Development of Sharia Finance Digitalization Towards Inclusive Finance Within a Sharia Maqashid Framework (Case Study on PT Bank Syariah Indonesia’s BSI Mobile Banking Product) - Angel Dwi Satria; Anita Anita; Krismadayanti Krismadayanti; Heni Noviarita (Journal of Islamic Business and Economic Review, 2021)
The level of Islamic financial literacy and inclusion in Indonesia is still relatively low, data from the Financial Services Authority (OJK) in 2020 shows that the level of Islamic financial literacy is around 8.93% compared to the national index of 76.19% and the level of Islamic financial inclusion is around 9.9%. has not reached 10%. This low public access can be overcome by combining financial services and products with the latest technology. This is an opportunity for the Islamic finance industry to innovate digitally. The author examines digital product innovation to increase literacy and inclusion of Islamic finance, namely the "BSI Mobile Banking" application with 15 features of Islamic financial services owned by PT Bank Syariah Indonesia Tbk. This study uses a qualitative analysis method that explains the suitability of 15 application features with the maqashid sharia concept (Dharuriyyah, Hajiyat and Tahsiniyat) and analyzes the implications of digital applications on Islamic financial literacy and inclusion. The results show that the digital innovation "BSI Mobile Banking" is in accordance with the maqashid sharia concept and can help increase the level of sharia financial literacy and inclusion and support halal needs according to sharia maqashid.